2000
DOI: 10.1106/qt5c-v941-nkjt-9xl2
|View full text |Cite
|
Sign up to set email alerts
|

Transient Interaction of Buildings with HVAC Systems— Updating the State of the Art

Abstract: This paper reviews work that has led to the development of a number of multi-zonal airflow models (network models). At present, the network analysis and perturbation methods cannot be used to solve the interstitial flow, pressure and resistance regimes. Network analysis and perturbation may suggest that such flows exist, but the complexity and workmanship dependence of the interstitial flow, pressure and resistance regime requires direct measurement. In other words, at present, the boundary conditions of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Only recently in Scandinavia and North America the focus shifted to frame walls and included effects of air flow. It was found that air flows carry more moisture than water vapor diffusion, and that air, in a manner similar to sound transmission, flowing across and along building partitions, may connect seemingly separate regions of the building (Lstiburek, 2000;Lstiburek et al, 2000 and2002). Furthermore, moisture carried by air is a major factor affecting durability of building materials.…”
Section: Effect Of Thermal Bridgesmentioning
confidence: 99%
“…Only recently in Scandinavia and North America the focus shifted to frame walls and included effects of air flow. It was found that air flows carry more moisture than water vapor diffusion, and that air, in a manner similar to sound transmission, flowing across and along building partitions, may connect seemingly separate regions of the building (Lstiburek, 2000;Lstiburek et al, 2000 and2002). Furthermore, moisture carried by air is a major factor affecting durability of building materials.…”
Section: Effect Of Thermal Bridgesmentioning
confidence: 99%
“…Measured directly on a section of the envelope, for example, using a box attached to the wall with window; Evaluated from multizonal network models and airflow perturbations (Lstiburek, 1998;Lstiburek et al, 2000Lstiburek et al, , 2002 or by similar method to separate the section from the surrounding space.…”
Section: Terminology Related To Absmentioning
confidence: 99%
“…The effect of pathways created by external cavities and interconnected internal cavities communicating with HVAC systems on performance of building systems is often neglected (Figure 4). The significance of these elements has been illustrated in the few examples selected from case studies (Lstiburek, 1995, 2002, Lstiburek et al, 2000. Some other cases listed by Lstiburek (1998) are as follows: A facility located in a cold climate with inadequate provision for return air.…”
Section: Need For Testing Airtightnessmentioning
confidence: 99%
“…Energy+) allow inclusion of two- or three-dimensional model segments, one does not use this facility for inclusion of the HT modeling as a subset of energy modeling. Despite many research articles (Bomberg and Thorsell, 2008; Kosny et al, 2007; Lstiburek, 1999; Lstiburek et al, 2000, 2002; Said et al, 1997; Tamura, 1975; Tamura et al, 1974; Tamura and Wilson, 1963, 1966, 1967; Thorsell and Bomberg, 2008, 2011) highlighting effects of air and moisture on energy calculations with exception of some discussed in International Energy Agency (IEA) Annex 41, the whole-building energy models do not include effects of air and moisture transfer through walls.…”
Section: Call For Better Toolsmentioning
confidence: 99%